It's complicated the social lives of networked teens - Boyd, Danah (Yale University Press, 2014)
What is new about how teenagers communicate through services such as Facebook, Twitter and Instagram? Does social media affect the quality of teens' lives? In this eye-opening book, youth culture and technology expert danah boyd uncovers some of the major myths regarding teens' use of social media. She explores tropes about identity, privacy, safety, danger and bullying. At the same time, she acknowledges that coming to terms with life in a networked era is not easy or obvious. In a technologically mediated world, life is bound to be complicated.